Potential Adjuvant Effects of Nigella sativa Seeds to Improve Specific Immunotherapy in Allergic Rhinitis Patients - GÜRBÜZ, BURÇAK; RAYAMAN, ERKAN; RAYAMAN, PERVİN; SOYOĞUL GÜRER, ÜMRAN (KARGER, 2010)
Objective: To investigate the effects of Nigella sativa seed supplementation on symptom levels, polymorphonuclear leukocyte (PMN) functions, lymphocyte subsets and hematological parameters of allergic rhinitis. Subjects and Methods: Twenty-four patients randomly selected from an experimental group of 31 (mean age 34 years) sensitive to house dust mites with allergic rhinitis and a control group of 8 healthy volunteers (mean age 23 years) were treated with allergen-specific immunotherapy in conventional doses for 30 days. After a month of immunotherapy, 12 of the 24 patients and the 8 healthy volunteers were given N. sativa seed supplementation (2 g/day orally) for 30 days. The remaining 12 patients continued only on immunotherapy during the same period. The other 7 patients were given 0.1 ml saline solution subcutaneously once a week as a placebo. The symptom scores, PMN functions, lymphocyte subsets and other hematological parameters were evaluated before and after all treatment periods. Results: There was a statistically significant increase in the phagocytic and intracellular killing tivities of PMNs of patients receiving specific immunotherapy, especially after the addition of N. sativa seed. The CD8 counts of patients receiving specific immunotherapy plus N. sativa seed supplementation significantly increased compared to patients receiving only specific immunotherapy. PMN functions of healthy volunteers significantly increased after N. sativa seed supplementation compared to baseline. Conclusion: N. sativa seed supplementation during specific immunotherapy of allergic rhinitis may be considered a potential adjuvant therapy. Copyright (C) 2010 S. Karger AG, Basel
Keywords: Nigella sativa; Phagocytosis; Intracellular killing activity; Allergic rhinitis; Active immunotherapy; MOUSE MODEL; BLACK SEED; THYMOQUINONE; CELLS; OIL